Life cycle sustainability impact categories for sustainable procurement - Oliveira, Daniel Felipe de [UNESP]; Souza, Ricardo Gabbay de [UNESP] (Elsevier, 2023)
Sustainable procurement depends on the definition of evaluation criteria when structuring selection processes for the most sustainable suppliers and products. Since a product or service may be associated with several sustainability impact categories throughout its life cycle, the procurement process may consider them as evaluation criteria. A recommended approach for such product evaluation is Life Cycle Sustainability Assessment (LCSA). The main objective of this study is to identify and catalogue general sustainability impact categories to be used as evaluation criteria in sustainable procurement. This research applied cognitive mapping, a tool in Problem Structuring Methods, based on a systematic literature review and interviews with 10 experts in the field. They also collaborated in the categorization and validation of the results. This study suggests a set of 58 midpoint and 14 endpoint sustainability categories, providing a contribution for different actors in society and supply chains, allowing them to evaluate supply options in sustainable procurement. The participation of experts enriched the understanding of the problem, allowing to observe a fourth sustainability dimension for procurement, comprising Supplier Governance and Compliance.
Keywords: Cognitive mapping; Life cycle sustainability assessment; Problem structuring methods; Supplier selection problem; Sustainability impact categories; Sustainable procurement